INCREASING CADRE KNOWLEDGE: HELPING WITH EMERGENCY CASES IN MADURESO VILLAGE - Astuti, Dyah Puji; Sumarni, S; Rahmadhani, Wulan; Anisa, Anjani Nur; Adelia, Putri (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2024)
Emergency events are unpredictable and in dire need of proper and accurate management. Emergency conditions can be life-threatening so that proper and accurate treatment can help save the patient's mental condition. Knowledge about the detection and management of emergency conditions should not only be owned by health workers but also the general public really needs to know the detection and early management of emergency cases. This activity was carried out for cadres in Madureso village. The aim of the activity was to increase efforts to detect cadres through knowledge before and after being given health education and simulations. The results of this activity were 100% an increase in knowledge of emergency assistance before and after health education was carried out